Analysis of Mixture Paste of Cassava Peel and Pineapple Peel as Electrolytes in Bio Battery - Julia Elisabeth Sitanggang; Nur Zahra Latifah; Opi Sopian; Ziyan Saputra; Asep Bayu Dani Nandiyanto; Sri Anggraeni (Universitas Pendidikan Indonesia (UPI), 2021)
This study investigated the effect of the ratio of the electrolyte paste mixture of cassava peel (CP) and pineapple peel (PP) on the voltage and current strength. In the experiments, prior to using, CP and PP biomass waste was cleaned then soaked for 30 minutes. Furthermore, the biomass waste is mashed and put into the test media according to the comparison. In this study, CP/PP compositions were varied with the value of 100: 0, 75:25, 50:50, 25:75, and 0: 100. The results showed that the highest electrolyte obtained by voltage and current strength with a ratio of 100: 0. The more CP comparisons used, the greater the voltage and strong current. This research is potentially used as one of the renewable alternative energies and can utilize existing biomass waste.This study investigated the effect of the ratio of the electrolyte paste mixture of cassava peel (CP) and pineapple peel (PP) on the voltage and current strength. In the experiments, prior to using, CP and PP biomass waste was cleaned then soaked for 30 minutes. Furthermore, the biomass waste is mashed and put into the test media according to the comparison. In this study, CP/PP compositions were varied with the value of 100: 0, 75:25, 50:50, 25:75, and 0: 100. The results showed that the highest electrolyte obtained by voltage and current strength with a ratio of 100: 0. The more CP comparisons used, the greater the voltage and strong current. This research is potentially used as one of the renewable alternative energies and can utilize existing biomass waste